2020
DOI: 10.1101/2020.08.20.20177535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Problematic usage of the internet and eating disorders: a multifaceted, systematic review and meta-analysis

Abstract: Eating disorders are widespread illnesses with significant impact. There is growing concern about how those at risk of eating disorders overuse online resources to their detriment. We conducted a pre-registered systematic review and meta-analysis of studies examining Problematic Usage of the Internet (PUI) and eating disorders. The meta-analysis comprised n=32,295 participants, in which PUI was correlated with significant eating disorder psychopathology Pearson r=0.22 (s.e.=0.04, p<0.001), body dissatisfact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 125 publications
(288 reference statements)
1
7
0
1
Order By: Relevance
“…The first result expands upon the existing literature for the association between EDS and EIU [ 4 ] in that these two risks remain partially correlated, pointing to other unexplained mechanisms (not included in the present study) that are responsible for their co-occurrence. We suggest that family-related factors (e.g., parental care, parental monitoring, family dysfunction, family eating habits) might be explanatory factors; indeed, former studies already reported its effects on EDS [ 35 ] as well as on EIU [ 36 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The first result expands upon the existing literature for the association between EDS and EIU [ 4 ] in that these two risks remain partially correlated, pointing to other unexplained mechanisms (not included in the present study) that are responsible for their co-occurrence. We suggest that family-related factors (e.g., parental care, parental monitoring, family dysfunction, family eating habits) might be explanatory factors; indeed, former studies already reported its effects on EDS [ 35 ] as well as on EIU [ 36 ].…”
Section: Discussionsupporting
confidence: 82%
“…This is surprising because boys and girls have different patterns of internet use. The most established digital media activity associated with EDS is social media use [ 4 ], which has a higher prevalence among girls [ 14 ] compared to boys, who are likely to play games [ 40 ]. But based on our results, we may hypothetically assume that the associations among the studied constructs are similar regardless of the preferred digital activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various hypotheses were formulated by conducting an extensive literature review and empirical evidence is presented to support these relationships. In the past, researchers and scholars have investigated PUI and its various terrifying facets (Ioannidis et al, 2021;Ioannidis et al, 2020;Cheng et al, 2018;Mingoia et al, 2017;Sari and Aydin, 2014). However, a study that connects PUI with so many different variables is rare to find.…”
Section: Research Gap and Research Questionsmentioning
confidence: 99%
“…al., 2021). В одном из исследований была показана взаимосвязь между использованием Интернета и симптомами расстройств пищевого поведения, в частности: неудовлетворенностью телом, ограничительным питанием и стремлением к худобе (Ioannidis, et. al., 2020).…”
Section: Psychologyunclassified